The impact of institutional quality, market openness, and government size on corruption across income levels - Kusuma, Hendra; Iskandar, Deden (Program Magister Ilmu Ekonomi Pascasarjana Universitas Jambi, 2025)
Government openness in managing the economy can stimulate growth, but carries the risk of policy misuse. This study analyzes panel data from 139 countries between 2012 and 2023 to examine the relationship between economic openness and corruption, as measured by the Corruption Perceptions Index (CPI). The findings reveal that key factors such as government integrity and financial freedom significantly influence CPI scores across countries with varying income levels. Nations characterized by flexible business regulations, transparent governance, strong legal protection of property rights, and stable monetary policies tend to exhibit lower levels of public sector corruption. However, the analysis also shows that financial freedom in high-income countries and investment freedom in upper-middle-income countries are negatively associated with CPI scores. This suggests that excessive liberalization—particularly in investment—without adequate regulatory oversight can increase corruption risks, likely due to limited transparency in capital flows and foreign investment practices. In contrast, when properly managed, the recognition of property rights, government integrity, and investment freedom are instrumental in reducing corruption in many middle-income countries. The study highlights the importance of strengthening government integrity, particularly in delivering public services and regulating an open economy. By ensuring effective and efficient oversight, countries can enhance their CPI scores and reduce the potential for corruption.